Approaches In Islamic Education - Niko Riyan Nugroho (Penerbit Hellow Pustaka, 2023)
The approach to Islamic education is the perspective used in interpreting Islamic religious values through education with the aim of forming whole human beings who believe in Allah SWT . Various approaches in Islamic education are: Rational approach , emotional approach , holistic approach , systems approach , historical approach . The aspects that abstract the approach are: a philosophical aspect , an epistemological aspect and a pedagogical aspect.